Theoretical description of pressure-induced phase transitions: A case study of Ti-V alloys - Abrikosov, I.; Ponomareva, A.; Nikonov, A.; Zharmukhambetova, A.; Mosyagin, I.; Lugovskoy, Andrey; Hellman, O.; Lind, H.; Dmitriev, A.; Barannikova, S. (Taylor and Francis Ltd., 2015)
We discuss theoretical description of pressure-induced phase transitions by means of first-principles calculations in the framework of density functional theory. We illustrate applications of theoretical tools that allow one to take into account configurational and vibrational disorders, considering Ti-V alloys as a model system. The universality of the first-principles theory allows us to apply it in studies of different phenomena that occur in the Ti-V system upon compression. Besides the transitions between different crystal structures, we discuss isostructural transitions in bcc Ti-V alloys. Moreover, we present arguments for possible electronic transitions in this system, which may explain peculiar behaviour of elastic properties of V upon compression.